PLASMA ANALYSIS IN EQUILIBRIUM STATE IN ITER FUSION REACTOR USING BOUNDARY ELEMENT METH - ALWI TAMA (NIM : 10214009), DIVA
Plasma analysis of fusion reactors requires very fast data preparation and modification following the plasma changes occurring in the reactor. Therefore, the Boundary Element method is used to perform analysis on plasma in equilibrium state expressed through the Grad-Shafranov equation. Boundary element method analyzes the entire domains by considering boundary area, not by considering the domains directly so provide faster result. In this final project, a case review on the ITER fusion reactor plasma with 2 Current Profile criteria, namely Solov'ev and nonlinear. ITER reactor parameters are used to resolve the Grad – Shafranov equation. The completion process is carried out by expanding µ?rj? from level 1 to level 6. Variations in parameters ?? and ? on nonlinear criteria are carried out to analyze the effects caused by plasma. The results obtained showed that the Boundary Element method succeeded in producing the same Poloidal Magnetic Flux contour that was produced analytically on the Solov'ev criterion with an error ? 2% in the middle area, and ? 5% for the area near the boundary. In the nonlinear criteria, the results of Poloidal Magnetic Flux are convergent with the required iterations ?10 . Variations of ?? affect the maximum peak position of the Poloidal Magnetic Flux and Current Density, while the variation of ? affects the current density distribution in the plasma.